2014
DOI: 10.4321/s1578-84232014000100011
|View full text |Cite
|
Sign up to set email alerts
|

Las mujeres en la prensa deportiva: dos perfiles

Abstract: RESUMEN:El propósito del presente estudio fue analizar la imagen que la prensa deportiva española transmite de las mujeres y cómo ha evolucionado en los últimos años (1979 -2010). Para ello, se realizó un análisis de las informaciones donde al menos aparecía una mujer (n = 4877) en los cuatro periódicos deportivos de mayor tirada. Y dentro de las informaciones se analizaron a los protagonistas (hombres o mujeres) (n= 20928) y se examinando siete variables para determinar los perfiles de mujer (n= 12195) que pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 3 publications
2
7
0
15
Order By: Relevance
“…This fact has repercussions on the stereotyping of women and renders female athlete role models invisible. These women are, fundamentally, the subject of news or information that is not about any sport (58.41%) or related to football and football players (30.97%), a practice previously verified in studies carried out on print media in Spain between 1979-2010 [49] and which in print is tending to disappear, as the study revealed for the years 2017-2018 [40]. Nevertheless, on the Internet, its expansion is notable [51] and our research study demonstrates this increase in Twitter (V = 0.802).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This fact has repercussions on the stereotyping of women and renders female athlete role models invisible. These women are, fundamentally, the subject of news or information that is not about any sport (58.41%) or related to football and football players (30.97%), a practice previously verified in studies carried out on print media in Spain between 1979-2010 [49] and which in print is tending to disappear, as the study revealed for the years 2017-2018 [40]. Nevertheless, on the Internet, its expansion is notable [51] and our research study demonstrates this increase in Twitter (V = 0.802).…”
Section: Discussionmentioning
confidence: 91%
“…For the content analysis, an analysis sheet with six items was used: date, communication media, sport, photo, gender represented, and in the tweets about a woman, whether the analysis differentiates between two profiles for women: athletes and non-athletes (relatives of male athletes, well-known women and celebrities, etc.) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, children usually spend many hours in a seated posture. In fact, they usually spend around 60% and 80% of their school day in a sitting position [18,19]. Additionally, the time that is spent on homework and activities such as watching TV, using the computer, and playing on a tablet can be added to that seated time.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados sobre el poco protagonismo que tienen las mujeres deportistas en la cobertura deportiva están en consonancia con la cobertura mediática tradicional de los acontecimientos deportivos femeninos (Sainz de Baranda, 2014aBaranda, , 2014bBaranda, , 2014cSmallwood, Brown y Billings, 2014;Fink, 2015; Calvo-Ortega y Gutiérrez-San Miguel, 2016; Hall y Oglesby, 2016; Barbero, 2017; Gómez-Colell, Medina-Bravo y Ramón, 2017; Matud, Rodríguez-Wangüemert y Espinosa, 2017; Gómez-Collell, Medina-Bravo y Ramon, 2017; Mayoral y Mera, 2017; Adá-Lameiras, 2019; Adá-Lameiras y Rodríguez-Castro, 2020). Si bien se está analizando la cobertura de una competición de un deporte de equipo, la mayoría de la cobertura informativa de los medios deportivos está dedicada a deportes colectivos como el fútbol o el baloncesto, pero no se produce la invisibilización de los deportistas masculinos (Sainz de Baranda, 2013Baranda, , 2018.…”
Section: Discussionunclassified